IPTEKS PENGUKURAN KINERJA KEUANGAN PADA PT. PLN (PERSERO) WILAYAH SULUTTENGGO - Pinontoan, Regina F.; Gerungai, Natalia Y. T. (Universitas Sam Ratulangi, 2018)
The measurement of financial performance based solely on balance sheet financial statements and profit and loss is able to provide information on the feasibility of a company on the obligations of external parties and also assets owned by the company. From the results of financial statement analysis using financial ratio analysis of PT. PLN (Persero)RegionÂ Sulutttenggo can evaluate the financial performance of companies that show unfavorable conditions where the value of the liquidity ratio is less stable and even decreases. Whereas the results of the calculation of leverage ratio and profitability ratio show fairly good conditions. Thus, the writer suggest that the management always evaluate in improving the company's financial performance.Keywords : financial statement, financial performance, financial ratios